Tārīkh Nash'at al-Ma'ājim al-'Arabiyyah - Agus Yasin; alif Cahya Setyadi (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2015)
The history of Arabic lexicography began in the first century of the Hijri era (seventh century CE). Since that period, Muslim scholars paid considerable attention to the vocabulary of the Qur'an, particularly to the words classified as gharīb (uncommon or difficult words), by interpreting and investigating their precise linguistic meanings. Among the earliest scholars who devoted themselves to Qur'anic interpretation, especially the explanation of gharīb al-Qur'an, was ʿAbd Allāh ibn ʿAbbās (d. 68 AH/687 CE). The spread of the Arabic language throughout the regions conquered by Muslims also raised concerns among scholars about the preservation of Arabic due to its contact with other languages. Consequently, they compiled dictionaries to preserve the language and to facilitate understanding among people whose tongues had become influenced by non-Arabic languages. Today, there is no doubt that the Arab world faces certain limitations in the field of lexicography when compared with the remarkable lexicographical advancement achieved in many European countries, where dictionary-making has been regarded as a national endeavor and has received extensive institutional support and resources. This article aims to examine the historical development of Arabic dictionaries across different periods of Arab history. It discusses the general historical background of Arabic lexicography, the stages of its development and renaissance from its earliest beginnings to the present day, as well as the major schools of Arabic lexicography.